2017
DOI: 10.1039/c6ra27244d
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid membrane biomaterials from self-assembly in polysaccharide and peptide amphiphile mixtures: controllable structural and mechanical properties and antimicrobial activity

Abstract: Macroscopic capsules, with tunable properties based on hierarchical self-assembly on multiple lengthscales, are prepared from the co-operative self-assembly of polysaccharide and peptide amphiphiles. Different formulations can be used to create flexible membrane sacs in solution, soft capsules or rigid free-standing capsules. Samples are prepared by injecting a solution containing sodium alginate, with or without graphene oxide (GO), into a matrix consisting of a solution containing the peptide amphiphile PA C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Peptide amphiphiles (PAs) have been widely investigated in these co‐assembling systems. Several studies have reported the co‐assembly of peptide amphiphiles with polysaccharides of opposite charge (heparin, hyaluronic acid, alginate, carrageenan), which resulted in the formation of diverse type of biomaterials such as sacs, membranes, microcapsules, and microparticles . MDPs have been also self‐assembled with negatively charged biopolymers such as heparin to form hydrogels or with hyaluronic acid (HA) to create patterned and periosteum‐like membranes.…”
Section: Self‐assembling Hydrogels Of Peptides With Biopolymersmentioning
confidence: 99%
“…Peptide amphiphiles (PAs) have been widely investigated in these co‐assembling systems. Several studies have reported the co‐assembly of peptide amphiphiles with polysaccharides of opposite charge (heparin, hyaluronic acid, alginate, carrageenan), which resulted in the formation of diverse type of biomaterials such as sacs, membranes, microcapsules, and microparticles . MDPs have been also self‐assembled with negatively charged biopolymers such as heparin to form hydrogels or with hyaluronic acid (HA) to create patterned and periosteum‐like membranes.…”
Section: Self‐assembling Hydrogels Of Peptides With Biopolymersmentioning
confidence: 99%
“…59 Castelletto et al reported the observation of hydrogels for three lipidated peptides containing a lumican peptide sequence and three different lipid chain lengths (C12-, C14-and C16-) by pH adjustment. 60 Uniquely, these hydrogels are based on nanotape structures rather than cylindrical fibrils. A recent report shows that it is possible to create hydrogels from -helical peptides by careful design of the sequence.…”
Section: Hydrogel Studiesmentioning
confidence: 99%
“…For example, cathelicidin LL-37 has been grafted on silanized titanium surfaces, and the final material presents selective activity against E. coli strain K12 [47]. Another example is the lipopeptide C 16 -KKFF anchored in hybrid biomaterial membranes that generate capsules that are active against Listeria monocytogenes , S. aureus , and E. faecalis [48]. Immobilized antimicrobial peptides with antibiofilm activity have also been described, including peptide CWR11 immobilized on catheters via a polydopamine-peptide strategy, which exhibits activity against E. coli , S. aureus , and P. aeruginosa [49].…”
Section: Precision Antimicrobials: Bringing Precision Medicine To Infmentioning
confidence: 99%